Hospital solid waste management during COVID 19 pandemic in Nepal - Sharma G, Ram Prasad; Mehta, Raj Kumar; Angadi, Siddeshwar (Journal of Chitwan Medical College, 2020)
A newly discovered Novel Coronavirus is spreading across the world and is transforming the way, we sustain every day. COVID-19 pandemic has created challenges for international and national organizational level. Additionally, healthcare institution has many challenges to deal with COVID-19, especially in developing countries. Among the various challenges faced by healthcare institution, management of waste generated from treatment of COVID-19 patients is essential to prevent further impact on environment. Improper management of COVID-19 waste can lead to adverse public health ramification. Thus, good nationwide protocol and policies of waste management can play a vital role in protecting the health of nation and community.